Artisanal and Small-Scale Mining as a challenge and possible contributor to Sustainable Development - Zvarivadza, T. (Elsevier, 2022)
This paper explores the different challenges posed by Artisanal and Small-scale Mining (ASM) to Sustainable Development (SD), as well as proactive and unrealistic approaches in dealing with these challenges. Since there is no clear cut internationally acceptable definition of ASM, this paper considers ASM as the exploitation of marginal ore deposits, which are not profitable to mine on a large scale, through both informal (I/ASM) and formal channels (F/ASM) using rudimentary tools. I/ASM is illegal while F/ASM is legal and its activities are conducted under the approval of the presiding government. It is mainly I/ASM that poses disastrous challenges to SD. These can be classified into social, economic, environmental, safety and health and political challenges as expressed in the text.